Albanian Land Market Action Plan : purposes, achievements, lessons - Jazoj, Ahmet; Stanfield, David; Barry, Teresa; University of Wisconsin--Madison. Land Tenure Center.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
The transition in Eastern Europe and the Commonwealth of Independent States from command to market-oriented economies requires new land market institutions and policies. Once privatization of land has moved far enough to permit and stimulate demand for market transactions, the question becomes one of establishing dynamic land markets (i.e., a growing volume of transactions) that also "work properly." Concerning the transition in the ownership and management of real property and the resultant efforts to create new land market institutions, the experience of Albania is instructive, and this paper outlines the establishment of an Albanian land market strategy. In the discussion of a market-oriented economy in Albania, the question was how to create the land market component of the transition following privatization of land. Four market characteristics were identified as goals: (1) the land market should be dynamic, that is, there should be numerous transactions; (2) acquisition of land through these transactions should be by people who make productive investments; (3) all sectors of the population should participate in the market as buyers and sellers of land rights; and (4) people's investments in land through these market transactions should result in sustainable uses of land so as to assure the environmental rights of future generations. This paper presents the effort to address these goals through the Land Market Action Plan, prepared by Albanian government with the assistance of the Land Tenure Center.
iii, 32 p.
Keywords: Land titles Registration and transfer Albania; Land use Government policy Albania; Institution building Albania Evaluation; Technical assistance Albania Evaluation; Land administration Albania; Project appraisal Albania; Land markets Albania